Dystocia due to Acute Dorsal Deviation of Foetal Head and Neck along with Bilateral Shoulder Flexion in a Murrah Buffalo: A Case Report - Biswas, Newton; Kumar, Brijesh; Srivastava, Neeraj; Warghat, Chinmay Ruprao; Singh, Kiran; Kumar, Sushil; Dwivedi, Poornima (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Dystocia is one of the major causes of reproductive complications in buffaloes (Juneja et al., 2023). Dystocia is the term used to describe a delay or difficulty in parturition (Lombard et al., 2007; Purohit et al., 2012). The incidence of dystocia in buffaloes ranges from 2.12% to 4.81% (Prasad and Prasad, 1998; Khan et al., 2009). It may originate either from the maternal or foetal side (Noakes et al., 2009). Foetal causes of dystocia are usually evident at the time of parturition (Kaushish and Mathur 2005). Among the foetal causes, dystocia due to foetal mal-disposition is most commonly encountered, with an incidence rate ranging from 9.04-56.7% (Das et al., 2009; Mudasir et al., 2010; Shisodiya and Mali, 2014). Foetal mal-dispositions, such as the deviation of the head and neck of foetus in anterior presentation, are the most obvious reasons for dystocia